Biological activity of the Helicobacter pylori virulence factor CagA is determined by variation in the tyrosine phosphorylation sites - Higashi, Hideaki (National Academy of Sciences, 2002)
Helicobacter pylori is a causative agent of gastritis and peptic ulcer. cagA(+) H. pylori strains are more virulent than cagA(−) strains and are associated with gastric carcinoma. The cagA gene product, CagA, is injected by the bacterium into gastric epithelial cells and subsequently undergoes tyrosine phosphorylation. The phosphorylated CagA specifically binds SHP-2 phosphatase, activates the phosphatase activity, and thereby induces morphological transformation of cells. CagA proteins of most Western H. pylori isolates have a 34-amino acid sequence that variably repeats among different strains. Here, we show that the repeat sequence contains a tyrosine phosphorylation site. CagA proteins having more repeats were found to undergo greater tyrosine phosphorylation, to exhibit increased SHP-2 binding, and to induce greater morphological changes. In contrast, predominant CagA proteins specified by H. pylori strains isolated in East Asia, where gastric carcinoma is prevalent, had a distinct tyrosine phosphorylation sequence at the region corresponding to the repeat sequence of Western CagA. This East Asian-specific sequence conferred stronger SHP-2 binding and morphologically transforming activities to Western CagA. Finally, a critical amino acid residue that determines SHP-2 binding activity among different CagA proteins was identified. Our results indicate that the potential of individual CagA to perturb host-cell functions is determined by the degree of SHP-2 binding activity, which depends in turn on the number and sequences of tyrosine phosphorylation sites. The presence of distinctly structured CagA proteins in Western and East Asian H. pylori isolates may underlie the strikingly different incidences of gastric carcinoma in these two geographic areas.